A Decomposability Property to the Weighted Myerson Value and the Weighted Position Value. (3rd February 2021) - Wang, Guangming; Shan, Erfang
Abstract : Myerson value and position value are important values in a cooperative game with a graph structure. Usually, due to the differences of players in the game, the weighted Myerson value and weighted position value are more widely used in practical situations. This article offers a new calculation approach of the weighted Myerson value and weighted position value. Instead of using induced games (point game and edge game), we prove that the weighted Myerson value and weighted position value meet decomposability property.